Child Protection in Ballet: Experiences and Views of Teachers, Administrators and Ballet Students. (13th November 2012) - Papaefstathiou, Maria; Rhind, Daniel; Brackenridge, Celia
<x xml:space="preserve">Abstract</x> Over the past 15 years, there has been a growing concern regarding child protection (CP) in the sport context yet there remains a lack of research into how key stakeholders view related CP policies. The present exploratory case study of a UK ballet organisation focuses on the following research questions: (1) What are the key elements of good practice for CP in ballet? and (2) Which discourses are adopted by ballet stakeholders when discussing CP‐related experiences? Semi‐structured interviews and self‐report semi‐structured questionnaires were conducted with 13 stakeholders drawn from ballet teachers, students and administrators. Inductive analysis revealed five welfare discourses: positive, neutral, negative, contradictory and rationalising. A tendency to normalise negative experiences in ballet was also identified. The CP‐related policy knowledge of teachers and administrators was generally satisfactory with some gaps being highlighted. Recommendations for implementation of CP policy in ballet are outlined. Copyright © 2012 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2228-blk-0001" position="anchor" orientation="portrait"> 'Semi‐structured interviews and self‐report semi‐structured questionnaires were conducted with 13 stakeholders' </boxed-text> Key Practitioner Messages There is growing concern for CP in contexts which attract the participation of children. Aesthetic activities, such as ballet, have been identified as facing welfare issues. Ballet students' experiences can vary, thus indicating a need for CP policy implementation. Elements of good practice for CP indicate a safe environment. Recommendations for preventative and proactive CP policy implementation are outlined.